Study of some effective factors on the production of garamicidin from locally isolated Bacillus brevis (Baghdad Science Journal, 2007)
The optimum cultural conditions for garamicidin production by local isolate B.brevis were studied.Best result was obtained when the isolate B.brevis was grown on media composed of 1%glucose as carbon source,1% ammonium chloride as a nitrogen source ,0.5% Dipotassium hydrogen orthophosphate as a phosphate source and after 48 hours of incubation at 30C .Garamicidin has been extracted and purified through acid precipition and then extracted by organic solvent (ether& acetone ).Using HPLC the garamicidin antibiotic showed three types A,B and C garamicidin .